Ca2+-dependent hyperpolarization hypothesis for mammalian sleep. (May 2017) - Tatsuki, Fumiya; Ode, Koji L.; Ueda, Hiroki R.
Highlights: Sleep/wake cycles are characterized by a wide range of time scales. A Ca 2+ -dependent hyperpolarization mechanism can explain the slow-wave oscillation. The hyperpolarization mechanism may undergo slow regulation by kinases and SISs. The hyperpolarization mechanism can connect fast and slow NREM-sleep dynamics. Abstract: The detailed molecular mechanisms underlying the regulation of sleep/wake cycles in mammals are elusive. In this regulation, at least two mechanisms with fast and slow time scales are involved. In the faster time scale, a state of non-rapid-eye-movement (NREM) sleep can be microscopically characterized by the millisecond-to-second-order electrical behavior of neurons, namely slow-wave oscillations described by electrophysiology. In the slower time scale, the total duration of NREM sleep is homeostatically regulated by sleep pressure (the need for sleep), which is usually sustained for hours or even days and can be macroscopically described by electroencephalogram (EEG). The longer dynamics of sleep regulation are often explained by the accumulation of sleep-inducing substances (SISs). However, we still do not have a concrete model to connect fast, microscopic dynamics and slow, macroscopic dynamics. In this review, we introduce a recent Ca 2+ -dependent hyperpolarization hypothesis, in which the Ca 2+ -dependent hyperpolarization of cortical-membrane potential induces slow-wave oscillation. Slow dynamics of the Ca 2+ -dependent hyperpolarization pathway might be regulated by recently identified sleep-promoting kinases as well as classical SISs. Therefore, cortical Ca 2+ -dependent hyperpolarization may be a fundamental mechanism connecting fast neural activity to the slow dynamics of sleep pressure.